2014
DOI: 10.1245/s10434-014-4265-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of Blood Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in Gastrointestinal Stromal Tumors

Abstract: High PLR was associated with reduced RFS. The prognostic ability of PLR to predict recurrence suggests that it may play a role in risk-stratification schemes used to determine which patients will benefit from adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 34 publications
5
49
2
Order By: Relevance
“…The results in our present study showed that high level of PLR was associated with poor prognosis of GISTs. This was consistent with the studies reported by Racz et al 14 and Goh et al 16 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results in our present study showed that high level of PLR was associated with poor prognosis of GISTs. This was consistent with the studies reported by Racz et al 14 and Goh et al 16 …”
Section: Discussionsupporting
confidence: 93%
“…Among them, Perez et al 12 Atila et al, 13 Kargin et al, 15 and Goh et al 16 showed that high level of NLR was correlated with poor prognosis of GISTs. No correlation between NLR and prognosis of GISTs was found in the study reported by Racz et al 14 This may attribute to the relatively small sample size of the study. In our present study, we also found that high NLR was associated with poor prognosis of GISTs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, a cutoff point simply determined by ROC curve in our study may not be appropriate to estimate the prognostic value of platelet counts. PLR, which take both protumor status and antitumor immune status into consideration, has emerged as an independent prognostic factor in many cancers . However, there were no studies regarding its prognostic role in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the last few years, the combination of inflammatory markers or inflammation-based prognostic scores, including the neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR) 7-9, lymphocyte monocyte ratio (LMR) 10, and prognostic nutritional index (PNI) 11, have been reported to have prognostic value in patients with various cancer.…”
Section: Introductionmentioning
confidence: 99%